Accessibility and utility of agricultural market information in Alamata and Atsbi-Wemberta Pilot Learning Weredas, Tigray, Ethiopia - Okubay, T. (Mekelle University, 2009)
Introducing and promoting the production of marketable commodities require adequate, accurate, relevant and timely information. Noting the background of poor market information provision efforts in the country and the new regional initiative on the other hand, it was necessary to conduct this research aimed at studying the availability, accessibility, and utility of agricultural market information in Alamata and Atsbi- Wemberta pilot learning weredas. Assessing the sources of market information; investigating the process of market data collection up to broadcasting on radio; and studying accessibility the utility of market information are the specific objectives. Primary and secondary sources as well as quantitative and qualitative information were collected. Systematic random sampling method was used to select 141 households for interview. From the random sample, only 18 households were able to comment on the MI received form radio. Therefore, additional 10 radio listeners were interviewed to increase the sample size of radio listeners. Information was also collected from experts working at wereda and region levels as well as from DAs and cooperatives. Radio, information display boards, cooperatives (for marketing-in products) bulletin and website of TAMPA, are the formal media of MI. Out of these, MI broadcasted on local radio and MI placed on display boards are assumed to be accessed by farmers and other rural households. The results of the study showed, HHs with practical access (who actually were able to comment on the MI on radio) were only 12.8 percent of the randomly selected households though HHs having access to radio account for 47.5 percent. The functionality of MI service using display boards is very poor, so far. The role of extension agents as well as cooperatives in disseminating MI to the local farmers/traders is minimal and seasonal. The media of MI frequently used by farming households and farmer-traders are weekly market visits and information exchange among farmers/traders. Telephone is used by few farmers/farmer-traders while wholesalers and cooperatives use it widely. The overall access scale to MI, for the majority of randomly selected households, is below ‘medium’ scale whereas satisfaction on the usefulness of MI received from radio is ‘high’ scale for the majority of respondents (able to comment on the radio MI service). In sum, accessibility and utility of MI could be improved by ensuring better management and coordination of the available media and sources; by creating awareness on the availability of these resources and how to use them; by improving the quality of access to MI; by improving networks and coordination among the formal and non-formal medium of MI; and ensuring the continuity of the service by allocating regular budget. Monitoring MI quality dimensions and considering the use of ICT are also among the recommendations.